The Influence of Brand Image and Price on Purchasing Decisions Teh Pucuk Harum At BORMA Cibaduyut Department Store ( Study On BORMA Department Store Employees & Consumers (Cibaduyut, Bandung) - Aditya, Tri Destian; Rachmansyah, Arief (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Study This aims To analyze the influence of the brand's image and price on the decision to purchase Teh Pucuk Harum product at BORMA Cibaduyut Department Store, Bandung. With increasing competition in the tea market packaging Ready drinks, consumers have become more selective in choosing products. The method used in the study is an analysis of multiple linear regression with a sample of BORMA Toserba employees and consumers of Cibaduyut. Analysis results show that the image brand's own influence is positive and significant to decision purchase, with a coefficient regression of 0.662. While that, price also has an effect positive and significant with a coefficient regression of 0.345. The F test shows that, in a way, simultaneous image brand and price significantly influence decision purchases, explaining 54% of the variation in decision purchases. Research This concludes that To increase the decision to purchase Teh Pucuk Harum, the company needs to strengthen its image brands and offer competitive prices